DIFFERENT CHARACTERISTICS BRAKE AUTOMOTIVE SYSTEM SALES RESEARCH MANUFACTURED BY ADDITIVE TECHNOLOGIES (Academic journal Industrial Machine Building Civil Engineering, 2019)
Problems in designing hydraulic brake systems of cars have been analyzed. The study of the braking process has conductedconsidering the distribution of forces on the axles during braking. The general support model research and support geometriccharacteristics are developed. The calculation of the car brake system has been conducted that enables to determine the load onthe caliper during the braking process and using graphic dependencies, and to determine the concentration of maximumstresses in the mounting areas of the support. Based on analytical studies in the Autodesk Fusion 360 3D Modeling program,a design has been implemented that features a smaller metal capacity at the expense of rational design and providing uniformstrength across the entire surface. Adaptive technologies also significantly accelerate the production of new parts due to thelack of need for the production of auxiliary equipment, such as molds.
Keywords: brake system of the car; additive technologies; support.